2022
DOI: 10.37908/mkutbd.1031079
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality parameters of the ‘Sabrina’ strawberry variety grown in soilless culture system during winter season

Abstract: The aim of this study is to determine the changes in fruit quality during the winter season of 'Sabrina' strawberry cultivar grown in soilless culture system in Antakya (Hatay) province. Methods and Results:In this study, 'Sabrina' strawberry variety was used as material. Within the study, amount of some contents such as; fruit weight, width and length, appearance (1-5), taste (1-9), fruit color L* and h° values, fruit flesh firmness, juice pH values, total soluble solids (TSS) content, titratable acidity (TA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Ozdemir et al ( 2022) [32] determined the total antioxidant capacity of the fruits of the 'Sabrina' strawberry variety grown in the "Kokopit" environment as an average of 10.42 mmol TE L -1 . Schöpplein et al ( 2002) [33] found in their study with 12 strawberry varieties that the antioxidant capacity varied between 8.40-16.50 mmol L -1 , while Gündüz and Özdemir (2014) [34] determined that it varied between 8.20-8.90 mmol TE L -1 .…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Ozdemir et al ( 2022) [32] determined the total antioxidant capacity of the fruits of the 'Sabrina' strawberry variety grown in the "Kokopit" environment as an average of 10.42 mmol TE L -1 . Schöpplein et al ( 2002) [33] found in their study with 12 strawberry varieties that the antioxidant capacity varied between 8.40-16.50 mmol L -1 , while Gündüz and Özdemir (2014) [34] determined that it varied between 8.20-8.90 mmol TE L -1 .…”
Section: Results and Disscussionmentioning
confidence: 99%